Engineering Acetobacterium wieringae for acetone production from syngas - Moreira, João Paulo Carvalho (2024)
Gas fermentation using acetogenic bacteria offers a sustainable alternative to fossil-based chemical production by converting waste gas streams, such as syngas (CO, H2, CO2), into valuable biocommodities. In this study, strain JM, a novel isolate of the acetogen Acetobacterium wieringae was engineered for autotrophic acetone production. Novel constitutive promoters native to A. wieringae JM were identified and characterized, expanding the genetic toolbox for this organism. These promoters, along with previously described promoters from Clostridium autoethanogenum, were used to control the expression of acetone production operon from C. acetobutylicum, leading to significant improvements in acetone titers. The use of multiple transcriptional units (TUs) for pathway gene expression further enhanced acetone production compared to a single operon. Additionally, the acetoacetyl-CoA acetate/butyrate CoA-transferase enzyme from C. beijerinckii was found to improve acetone production compared to its homolog from C. acetobutylicum. The plasmid-based expression system using the pMTL83151 vector (pCB102 replicon) demonstrated segregational stability and a consistent single-copy number under both selective and non-selective conditions. Fermentation conditions were optimized, with buffer capacity and gas availability identified as critical factors in batch fermentations. The physiology of autotrophic acetone production was further assessed utilizing different gas compositions which significantly impacted carbon flux to acetone. Under optimized conditions with a 20% CO syngas blend, the engineered A. wieringae JM [pAW_PFTL-APO] strain achieved an acetone titer of 41.3mM. This study establishes A. wieringae JM as a promising platform for sustainable acetone production from waste gases and provides a foundation for further development of gas-based biorefineries.